DISCONTINUOUS GALERKIN METHOD FOR TWO DIMENSION GORLOV TURBINE MODEL - PRASETYADI (NIM 20206002), A.
Discontinuous Galerkin Method is an extension of the continuous finite element. This method is used to compute the Gorlov turbine model of two dimensions using linear triangular elements. The model is assumed to be a viscous incompressible fluids system and have the continuity and Navier-Stokes equations as the governing equations. The codes are built under MATLAB version 7 and run using Celeron 1.7 GHz computer with 512 MB memory. The program was verified using system of sphere in incompressible fluid with Reynolds Number 40. The codes were used to get the flow of 10000 Reynolds fluids for Gorlov turbine. The result of computation for 40 Reynolds fluids is in agreement with other works. The boundary layer appeared around wall of object. The pattern of the change of vertical and horizontal velocities pointed it out. Out of the layer, the fluids flow as the far flow. The computation result of Gorlov turbine model does not show the wake effect between blades. The distances of blades which are far enough are the reasons. CDs (Drag Coefficient) and CLs (Lift Coefficient) of the Gorlov turbine blade profile (NACA 0017) bring non zero Torque. It shows that this turbine is selfstarting as claimed by the inventor.